2022
DOI: 10.1149/1945-7111/ac6143
|View full text |Cite
|
Sign up to set email alerts
|

An Emerging Machine Learning Strategy for the Fabrication of Nanozyme Sensor and Voltametric Determination of Benomyl In Agro-Products

Abstract: An emerging machine learning (ML) strategy for the fabrication of a nanozyme sensor based on multi-walled carbon nanotubes (MWCNTs)/graphene oxide (GO)/dendritic silver nanoparticles (AgNPs) nanohybrid and the voltametric determination of benomyl (BN) residues in tea and cucumber samples is proposed. Nanohybrid is prepared by the electrodeposition of dendritic AgNPs on the surface of MWCNTs/GO obtained by a simple mixed-strategy. The orthogonal experiment design combined with back propagation artificial neural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…Xu et al employed an orthogonal experimental design in combination with the BP artificial neural network-genetic algorithm (BP–ANN–GA) to assess the impact of four factors (volume ratio of graphene oxide (GO) and multi-walled carbon nanotubes (MWCNTs), silver nitrate concentration, CV deposition cycle, and pH of phosphate buffer) on the peak current value (I) of benzyl (BN). 60 This approach aimed to optimize the preparation technique for the nanozyme-based sensor and determine the optimal experimental conditions. Under these conditions, the nanozymes catalysed a BN reaction on the working electrode, generating an electrical signal.…”
Section: In Nanozyme Applicationsmentioning
confidence: 99%
“…Xu et al employed an orthogonal experimental design in combination with the BP artificial neural network-genetic algorithm (BP–ANN–GA) to assess the impact of four factors (volume ratio of graphene oxide (GO) and multi-walled carbon nanotubes (MWCNTs), silver nitrate concentration, CV deposition cycle, and pH of phosphate buffer) on the peak current value (I) of benzyl (BN). 60 This approach aimed to optimize the preparation technique for the nanozyme-based sensor and determine the optimal experimental conditions. Under these conditions, the nanozymes catalysed a BN reaction on the working electrode, generating an electrical signal.…”
Section: In Nanozyme Applicationsmentioning
confidence: 99%
“…[79][80][81] Recently, multiple machine learning algorithms have been exploited to help constructing nanozyme-based sensors. [82][83][84] By virtue of machine learning, nanozyme sensors with polytype of output signals, meanwhile the signals could be processed simultaneously within one smartphone, are highly expected, yet underdeveloped. It is due to machine learning algorithms rely on huge computing data, which is still difficult to be undertaken by smartphones at present.…”
Section: Electrochemical Signalmentioning
confidence: 99%
“…In fact, to achieve better selectivity and accuracy, nanozyme‐smartphone integrated sensing platforms with dual‐signal output modes instead of only one output signal were proposed, in which colorimetric‐electrochemical, colorimetric‐fluorescence and colorimetric‐Raman scattering have been reported [79–81] . Recently, multiple machine learning algorithms have been exploited to help constructing nanozyme‐based sensors [82–84] . By virtue of machine learning, nanozyme sensors with polytype of output signals, meanwhile the signals could be processed simultaneously within one smartphone, are highly expected, yet underdeveloped.…”
Section: Nanozyme Sensing Signals Used In the Smartphone Analysesmentioning
confidence: 99%
“…In previous studies, we found that assembled multi-walled carbon nanotubes (MWCNTs) could improve the electrocatalytic performance and stability of their composites. 26 Therefore, in this study, the ZSHPC/MWCNT/SPE sensor was prepared using the characteristics of MWCNT and ZSHPC materials for the detection of CBZ in agricultural products.…”
Section: Introductionmentioning
confidence: 99%